A study on the relationship between employee benefits and job satisfaction at Pacific Motor Sdn Bhd / Nur Adeera Roslan - Roslan, Nur Adeera (Faculty of Business Management, Universiti Teknologi MARA, 2019)
The study was conducted to investigate the relationship between employee benefits and job satisfaction at Pacific Motor Sdn Bhd. There are three elements of employee benefits that had been selected to be studied which are health benefits, salary and rewards that influence employees' job satisfaction. In order, to persue the research and collect data, questionnaires method had been used the total sample size of 56 employees. To analyze the data collected, Statiscal Package for the Social Science (SPSS) version 23.0 had been used. The results gained from the raw data showed that the two variables. From the findings, it showed that salary was highly affecting on the employees' job satisfaction among the employees at Pacific Motor Sdn Bhd. While, health benefits and rewards affected the least toward respondents' job satisfaction. The researcher also included some recommendations for the organization to provide better reward and health benefits to their employees in order to increase their job satisfaction, performance and productivity. At the same times, the researcher also came up with some suggestions for the future research.